PENERAPAN MEDIA PERMAINAN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS IX-K SMP NEGERI 29 SURABAYA - Alaauddin, Miftaahul; Bangun Setiya, Muhammad; Arikatul Antikah, Millah; Ayu Larasati, Dian; Sriviyantiningrum, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted at SMP Negeri 29 Surabaya, where it is known that the problem faced by students is still low learning outcomes in Social Science lessons, so this research tries to provide solutions to the problems faced in SMP Negeri 29 Surabaya with the aim of improving student learning outcomes through the application of a cooperative learning model of the Teams Games Tournament (TGT) type as an effort to improve student learning outcomes in classes IX-K SMP Negeri 29 Surabaya in the even semester of the 2023/2024 academic year. The results showed that the implementation of the cooperative learning model of the teams games tournament (TGT) type had a positive impact on improving the learning outcomes of students in class IX K in social studies subjects. In cycle I, students who obtained complete learning outcomes amounted to 66% and in cycle II, students who obtained complete learning outcomes amounted to 80%. The Team Games Tournament (TGT) Type Cooperative Learning Model can improve the learning outcomes of students in class IX K SMP Negeri 29 Surabaya.